An exploration of the factors that impact on clinical practices of Nurses in applying evidence-based practice - Fathimath Shifaza; Mohammad Hamiduzzaman (International Journal of Advanced Health Science and Technology, 2021)
While healthcare institutions around the world strive to adopt evidence-based practice (EBP) as the new standard in best practice, the nursing profession still faces multiple barriers and limitations in implementation. The aim of this paper is to present the analysis of EBP from the perspective of nurses working within two major South Australian hospitals, assessing their implementation and beliefs and exploring avenues for further research-based upon their feedback. A descriptive survey using the EBP beliefs (EBP-b) and the EBP implementation (EBP-I) scales were developed by Melnyk and Fineout-Overholt. Nurses scored high in the EBP belief scale reflecting significant positive readiness towards EBP. A positive correlation was observed between EBP beliefs and implementation, yet implementation rates were very low. More research is needed to explore the reasons why implementation rates are so low amongst practising nurses to understand and address the root of this problem. Based on the evidence it appears that more research is needed to explore the reasons why implementation rates are so low amongst practising nurses to understand and address the root of this problem.